European Rating Actions, Investor Reaction, and Bond Spread Volatility. (14th May 2015) - Ory, Jean‐Noël; Raimbourg, Philippe
<x xml:space="preserve">Abstract</x> This paper uses unit root tests that allow for structural breaks in order to examine the impact of ratings announcements on European bond credit spreads. In general, there are no noticeable reactions to announcements for issues in euros, which comes in contrast to the results of previous studies on US corporate bonds. However, we have noticed a reaction to rating actions for issues in sterling. In the case of a reaction to a downgrade or a negative watch, investor reaction generally occurs before the rating announcement, and negative watches are anticipated by investors a little more frequently than downgrades. For this type of event, we see a decrease in spread volatility after the rating announcements, as if the action of the rating agency confirms the informed investors' perception of default risk, and in doing so, stabilizes spreads and reduces spread volatilities.